PERAN SEKOLAH DALAM MELAKUKAN PEMBINAAN AKSI BALAP LIAR SEBAGAI KENAKALAN REMAJA: STUDI KASUS PADA SMA X KAMPAR - Nurwinda , Citra; Rinaldi, Kasmanto (Gapenas Publisher, 2024)
One of the features of adolescent recognition is wild racing. Wild racing is a high-speed activity (which exceeds the normal limits in the Traffic Act) whether it is a motorcycle or a car that does not meet national standards or equipment standards, performed on public tracks. The method in this research uses qualitative research which is research that can give a detailed description and analysis of the phenomena that occur. The school acts as a guide by advising, educating and being a good example to its students. As far as schools are concerned, these are: the implementation of sanctions on construction, the introduction of a full-day system, active extracurricular activities, strict school care, the participation of parents in the supervision of children, the provision of a persuasive approach to students. (Imtak Dan Literasi). There are two factors that most influence the onset of juvenile disability in wild racing, both external and internal. On the subject of this research uses social bonding theory which studies a social and personal relationship with other people or their surroundings. In the role of school with all kinds of efforts to minimize the rate of adolescent disability especially wild racing must have its own obstacles experienced. As is expected in the future, youth racing will be reduced and replaced by other positive activities.